(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
The cephalic index is a crucial anthropometric measurement used to classify head shapes and assess race in various pop ulations. It has broad applications in forensic anthropology, clinical craniofacial analysis, and anthropological research. This study aimed to determine the mean cephalic index among undergraduate medical students of Tripura Medical College who are permanent residents of Tripura, and to analyse differences based on gender and ethnicity. A total of 323 students participated, including 175 females and 148 males. Standard anthropometric tools were used to measure skull length and breadth, and the cephalic index was calculated as the ratio of maximum cranial breadth to maximum cranial length multiplied by 100. The mean cephalic index observed was 80.87 ± 3.49, indicating a predominance of the brachycephalic type (65%), followed by Mesocephalic (30%) and dolichocephalic (5%) skulls. Although females showed a slightly higher mean cephalic index (81.05 ± 3.48) compared to males (80.65 ± 3.50), the difference was not statistically significant (p = 0.315). However, a significant difference was found between ethnic groups, with non-Bengali students showing a higher mean cephalic index (81.75 ± 2.85) compared to Bengali students (80.44 ± 3.70) (p = 0.001). These results suggest that ethnicity plays a notable role in cranial morphology, whereas gender does not significantly influence cephalic index. The findings provide valuable regional data for forensic and clinical applications and contribute to the anthropometric profiling of populations in Northeast India.